MANAJEMEN SUMBER DAYA MANUSIA - Samsuni Samsuni (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Human resource management is planning, organizing, implementing and controlling human resources in an organization to achieve goals effectively and efficiently. Human resources as one of the existing resources in the organization play an important role in the successful achievement of organizational goals. Success or failure depends on the ability of human resources in carrying out their duties and functions